Penerapan Algoritma Punctured Elias Codes Pada File Transfer Berbasis Android - Muhammad Rezki Wasallam; Muhammad Syahrizal; Ilhamsyah Ilhamsyah (STMIK Budi Darma, 2022)
Text file size is sometimes relatively large where the better the quality of the resulting text file, the larger the file size needed to store the text file. With a very large text file size, when carrying out the transfer process the transfer process may fail because the media storage space exceeds the limit. The solution to this problem is how the text file can be compressed in order to speed up the transfer and storage of text files. Compression in text files is done by reducing the size of the text file by reducing the bits in the text file, but not eliminating the information data in it.By compressing, large data will be reduced in size so as to save storage space. In this study, the algorithm used is punctured elias codes, by using this algorithm, the compression results of the values have different results for each value, and the compression results will be beneficial in sending, and moving text files will be easier.